REFLEKSI SEJARAH ISLAM DINASTI UMAYYAH DARI ARABISASI HINGGA PENGEMBANGAN - Achmad Muzammil Alfan Nasrullah (Prodi PAI Fakultas Tarbiyah IAI Miftahul Ulum, 2022)
The Dinasty Umayyah was one of the leaderships that had contributed and ruled in advancing science and technology which was a form of its empire in its era. It also made many alterations that led to Advancement through its leaders from generation to generation.The research approach in this study uses qualitative, while this type of research is carried out using library research. The results of the research conclude that The establishment of the Dinasty Umayyah is built by political, cultural and scientific elements. In addition, the Dinasty Umayyah carries out an arabization system starting during the reigns of 'Abd al Malik and Al-Walid through breakthroughs in each generation.